Impact of protein pre-coating on the protein corona composition and nanoparticle cellular uptake. (January 2016) - Mirshafiee, Vahid; Kim, Raehyun; Park, Soyun; Mahmoudi, Morteza; Kraft, Mary L.
Abstract: Nanoparticles (NPs) are functionalized with targeting ligands to enable selectively delivering drugs to desired locations in the body. When these functionalized NPs enter the blood stream, plasma proteins bind to their surfaces, forming a protein corona that affects NP uptake and targeting efficiency. To address this problem, new strategies for directing the formation of a protein corona that has targeting capabilities are emerging. Here, we have investigated the feasibility of directing corona composition to promote targeted NP uptake by specific types of cells. We used the well-characterized process of opsonin-induced phagocytosis by macrophages as a simplified model of corona-mediated NP uptake by a desired cell type. We demonstrate that pre-coating silica NPs with gamma-globulins (γ-globulins) produced a protein corona that was enriched with opsonins, such as immunoglobulins. Although immunoglobulins are ligands that bind to receptors on macrophages and elicit phagocytois, the opsonin-rich protein corona did not increase NP uptake by macrophage RAW 264.7 cells. Immunolabeling experiments indicated that the binding of opsonins to their target cell surface receptors was impeded by other proteins in the corona. Thus, corona-mediated NP targeting strategies must optimize both the recruitment of the desired plasma proteins as well as their accessibility and orientation in the corona layer.